2008
DOI: 10.1074/jbc.m704748200
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Dehydrogenase Complex Deficiency Caused by Ubiquitination and Proteasome-mediated Degradation of the E1β Subunit

Abstract: Congenital deficiencies of the human pyruvate dehydrogenase (PDH) complex are considered to be due to loss of function mutations in one of the component enzymes. Here we describe a case of PDH deficiency associated with the PDH E1␤ subunit (PDHB) gene. The clinical phenotype of the patient was consistent with reported cases of PDH deficiency. Cultured skin fibroblasts demonstrated a 55% reduction in PDH activity and markedly decreased immunoreactivity for PDHB protein, compared with healthy controls. Surprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…The amino acid positions of the mutations are reported considering the mature NCBI protein sequence (NP_000275.1 for PDHA1 and NP_003468.2 for PDHX ) after signal peptide cleavage. # This patient was found to have PDH deficiency due to abnormal ubiquitination and proteasome degradation of E1β encoded by PDHB1 gene, as previously described (66). N.D.= not detected.…”
Section: Figmentioning
confidence: 54%
See 1 more Smart Citation
“…The amino acid positions of the mutations are reported considering the mature NCBI protein sequence (NP_000275.1 for PDHA1 and NP_003468.2 for PDHX ) after signal peptide cleavage. # This patient was found to have PDH deficiency due to abnormal ubiquitination and proteasome degradation of E1β encoded by PDHB1 gene, as previously described (66). N.D.= not detected.…”
Section: Figmentioning
confidence: 54%
“…The molecular defects of the corresponding patient cell lines are shown in Table 1. Patients 1-12 (dark gray bars) have mutations in PDHA1 , patient 13 (light gray bar) has PDHC deficiency due to abnormal ubiquitination and degradation of E1β (66), and patients 14 and 15 (black bars) have mutations in PDHX . *p<0.05.…”
Section: Figmentioning
confidence: 99%
“…24 While PDH activities can be reversibly regulated by PDK2-and PDK4-dependent phosphorylation, PDH has been identified recently as an ubiquitination target. 31 Thus, MuRF1 is an excellent candidate for PDH inhibition control in muscle via its E3 ubiquitin ligase activity. Since PDH is a multienzyme complex, further studies are required to dissect the interaction of MuRF1 and other MuRF family members with PDH and its subunits in more detail: While we identified the interaction of MuRF1 with the β (lipoamide) subunit of PDH β, our proteome studies identified the PDH α-E1 subunit as being downregulated in MuRF1-TG mice.…”
Section: Murf1 and Muscle Metabolismmentioning
confidence: 99%
“…Inhibition of PDH-E1α phosphorylation by dichloroacetate, a PDK inhibitor, decreases the E1α degradation and maximizes the PDH activity (35). In contrast, phosphorylation of PDH-E1β at tyrosine residues is associated with enhanced E1β degradation via ubiquitination and decreased PDH activity (57). Indeed, the most notable change in M1 Macs is NOTCH-dependent expression of the PDH-E1α protein.…”
Section: Notch Inhibition In Myeloid Cells Attenuates Hmacs M1 Activamentioning
confidence: 99%